Still life with bread crumbs : a novel - Quindlen, Anna (New York : Random House Trade Paperbacks, 2014)
Still Life with Bread Crumbs begins with an imagined gunshot and ends with a new tin roof. Between the two is a wry and knowing portrait of Rebecca Winter, a photographer whose work made her an unlikely heroine for many women. Her career is now descendant, her bank balance shaky, and she has fled the city for the middle of nowhere. There she discovers, in a tree stand with a roofer named Jim Bates, that what she sees through a camera lens is not all there is to life
Keywords: Life change events -- Fiction; Pastoral fiction; Love stories